Comparisons between bupropion and dexamphetamine in a range of in vivo tests exploring dopaminergic transmission - Bredeloux, P (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: In the present study we investigated, in a range of in vivo tests whether the antidepressant bupropion, and its metabolites shared the dopamine releasing effect of the chemically related dexamphetamine. EXPERIMENTAL APPROACH: We compared bupropion and dexamphetamine in different neurochemical (microdialysis, DOPAC and HVA contents) and behavioural tests, assessing their effects in animals pretreated with a variety of agents (reserpine, sodium hydroxy-4-butyrate or haloperidol) known to modify dopaminergic transmission. KEY RESULTS: In mice, dexamphetamine, like bupropion, increased at low doses and reduced at high doses, locomotor activity. Dexamphetamine restored the locomotor activity in mice made akinetic by either sodium hydroxy-4-butyrate or reserpine, whereas bupropion did not. Moreover, bupropion prevented the dexamphetamine-induced reversal of akinetic effects of reserpine. Haloperidol abolished the locomotor-stimulant effects of dexamphetamine but did not suppress stimulation by bupropion. In microdialysis experiments, in chloral hydrate anesthetized rats, low doses of dexamphetamine (1 mg kg(−1)) markedly increased the extracellular dopamine concentration in striatum (340%), while bupropion (100 mg kg(−1)) produced only a moderate increase (150%). Finally, in rat striatum, as well as in the nucleus accumbens, bupropion increased the effect of haloperidol on DOPAC and HVA concentrations, whereas dexamphetamine reduced these haloperidol effects. CONCLUSIONS AND IMPLICATIONS: Considering only dopaminergic transmission, our results demonstrated that bupropion and metabolites displayed in vivo, as did bupropion in vitro, an inhibition of dopamine uptake and, contrast to dexamphetamine, were devoid of dopamine releasing effects.